Evaluation of Sleep Quality, Work Stress and Related Factors in Hospital Office Workers - Güngördü, Nejdiye; Kurtul, Seher; Erdoğan, Mehmet Sarper (La Medicina del Lavoro, 2023)
Background: Occupational factors, working conditions, age, gender, exercise, acquired habits, and stress affect a person’s sleep quality. The aim of this study was to investigate sleep quality, work stress, and related factors among office workers in a hospital. Methods: This cross-sectional study was conducted with office workers actively working in a hospital. A questionnaire consisting of a sociodemographic data form, the Pittsburgh Sleep Quality Index (PSQI), and Swedish Workload-Control-Support Scale were used to assess the participants. Results: The mean of PSQI score was 4.32±2.40 and 27.2% of the participants had poor sleep quality. In the multivariate backward stepwise logistic regression analysis, it was found that shift workers were 1.73 times (95% CI: 1.02-2.91) more likely to have poor sleep quality, and a one-unit increase in work stress score increased the risk of having poor sleep quality by 2.59 times (95% CI: 1.37-4.87). An increase in age was found to decrease the risk of poor sleep quality in workers (OR =0.95; 95% CI: 0.93-0.98). Conclusion: This study suggests that reducing workload and increasing work control as well as enhancing social support will be effective in preventing sleep disturbances. It is important, however, in terms of providing guidance for hospital employees in planning future measures to improve working conditions.